Impact of COVID‐19 on maintenance haemodialysis patients: The Indian scenario. Issue 12 (12th August 2020) - Trivedi, Mayuri; Shingada, Aakash; Shah, Meera; Khanna, Umesh; Karnik, Niteen D.; Ramachandran, Raja
Abstract: There is a lack of data describing the impact of the novel coronavirus 19 pandemic on the patients of chronic kidney disease stage V‐dialysis (CKD V‐D) from resource‐limited countries. A growing body of literature describes an increased susceptibility of CKD V‐D to COVID‐19 with adverse outcomes in those with severe disease. In the current retrospective report, we elucidate the outcome in consecutive 37 CKD V‐D patients with COVID‐19 from two dialysis centres in Mumbai, India. Of the 37 patients included in the study, 56.7% of patients were asymptomatic or had mild disease and 27% presented with severe symptoms. The recovery rate was 63%, all those who presented with a severe disease succumbed to the infection. Thirty per cent of patients presented with an extended dialysis break due to various logistic and social issues. Though the overall clinical presentation and outcomes of this cohort from a limited resource setting mimic the global scenario, unique social and logistic issues are an additional burden to the patient, caregivers and the health‐care facilities, which may worsen the outcomes in the future as the pandemic continues to spread. SUMMARY AT A GLANCE: This retrospective report addresses the outcome in 37 dialysis patients with COVID‐19 infection in Mumbai, India. 56.7% were asymptomatic or had mild disease and 27% presented with severe symptoms. Eleven patients (29.7%) presented with a history of having missed their regular dialysis sessions, 6 patients (54.5%) was refused by primary HD center. Overall, 23 (62.1%) had a successful outcome and 14 (37.8%) died.